The role of material deprivations in determining ART adherence: Evidence from a conjoint analysis among HIV-positive adults in Uganda. - Uzaib Saya; Zachary Wagner; Barbara Mukasa; Peter Wabukala; Lillian Lunkuse; Sebastian Linnemayr (Public Library of Science (PLoS), 2022)
Despite sustained global scale-up of antiretroviral therapy (ART), adherence to ART remains low. Less than half of those in HIV care in Uganda achieve 85% adherence to their ART medication required for clinically meaningful viral suppression, leaving them at higher risk of transmission. Key barriers to ART adherence include poverty-related structural barriers that are inter-connected and occur simultaneously, making it challenging to examine and disentangle them empirically and in turn design effective interventions. Many people living with HIV (PLWH) make tradeoffs between these various barriers (e.g., between expenses for food or transportation) and these can influence long-term health behavior such as adherence to ART. To be able to estimate the distinct influence of key structural barriers related to poverty, we administered a conjoint analysis (CA) to 320 HIV-positive adults currently taking ART at an urban clinic in Uganda between July 2019 and September 2020. We varied the levels of four poverty-related attributes (food security, sleep deprivation, monthly income, and physical pain) that occur simultaneously and asked respondents how they would adhere to their medication under different combinations of attribute levels. This allows us to disentangle the effect of each attribute from one another and to assess their relative importance. We used regression analysis to estimate the effects of each attribute level and found that food security impacts expected adherence the most (treatment effect = 1.3; 95% CI 1.11-1.49, p<0.001), followed by income (treatment effect = 0.99; 95% CI 0.88-1.10, p<0.001. Sleep and pain also impact adherence, although by a smaller magnitude. Sub-group analyses conducted via regression analysis examine heterogeneity in results and suggest that the effects of material deprivations on expected adherence are greater among those with high levels of existing food insecurity. Results from this CA indicate that external factors inherent in the lives of the poor and unrelated to direct ART access can be important barriers to ART adherence. This study applies a CA (typically administered in marketing applications) among PLWH to better understand individual-level perceptions relating to poverty that often occur simultaneously. Policy interventions should address food insecurity and income to improve adherence among HIV-positive adults.